2009
DOI: 10.1007/s10750-009-9704-1
|View full text |Cite
|
Sign up to set email alerts
|

Micro-environmental factors and the endemism of bromeliad aquatic fauna

Abstract: Tank bromeliads harbour aquatic microcosms with many endemic species among their leaves. We performed a set of experiments to determine which factors maintain the bromeliad aquatic fauna in isolation from neighbouring ponds. We cultivated three invertebrates species (an ostracod, an annelid and a cladoceran) from a pond surrounded by terrestrial bromeliads in Southeastern Brazil and introduced them inside cleaned bromeliads, using recipients with the same volume as controls. The pH, conductivity and organism d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 17 publications
2
32
0
2
Order By: Relevance
“…Also water conditions between bromeliads and nearby located ponds were previously described to be different. For instance, some aquatic invertebrates, like the bromeliad ostracod (Elpidium bromeliarum) were only found in tank bromeliads (Lopez et al 2009), which differ in terms of specific composition compared to nearby ponds and swamps (Little and Hebert 1996). Consistent with our hypothesis, our results indicate that each tank bromeliad creates a unique island in the canopies with respect to its microbial community.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also water conditions between bromeliads and nearby located ponds were previously described to be different. For instance, some aquatic invertebrates, like the bromeliad ostracod (Elpidium bromeliarum) were only found in tank bromeliads (Lopez et al 2009), which differ in terms of specific composition compared to nearby ponds and swamps (Little and Hebert 1996). Consistent with our hypothesis, our results indicate that each tank bromeliad creates a unique island in the canopies with respect to its microbial community.…”
Section: Discussionsupporting
confidence: 88%
“…Along with our hypothesis we clearly observed differences in pH, carbon, nitrogen and oxygen concentration between plant slurries and especially carbon content revealed to be a major determinant for the bacterial, archaeal and methanogenic community composition. Carbon availability was already identified as one of the main drivers of microbial community structure in soil (Fierer et al 2003) and Lopez et al (2009) assumed that occasional organic matter inputs can induce a eutrophic condition in tank-bromeliads. In a previous study by Goffredi et al (2011b) it was shown that pH has an effect on the bacterial community composition and that a low water content and therefore an increased oxygen exposure, affected the bacterial and archaeal community composition in tank bromeliad slurry (Brandt et al 2014;Brandt 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the experiment duration was long enough for all taxa present in controls to colonize tanks in both treatments. The absence of differences in most of the ecological parameters evaluated and the dominance of few taxa in shaded and unshaded bromeliads reflect the ecological filters provided by the studied ecosystems (Lopez and Rios, 2001;Lopez et al, 2009;Marino et al, 2012), which selected the colonizing organisms and resulted in communities with similar structure and taxonomic composition.…”
Section: Discussionmentioning
confidence: 81%
“…Water tanks of bromeliads are dynamic and complex environments inhabited by communities of different organisms including endemic species (Benzing, 1990;Lopez et al, 2009;Whittman, 2000). The presence of trapped water and organic detritus (phytotelmata) in tanks formed in bromeliad leaf rosettes is a major source of nutrients for these organisms and communities associated with the phytotelmata (Richardson et al, 2000).…”
mentioning
confidence: 99%